Lifestyle behaviour in adolescence and musculoskeletal pain 11 years later: The Trøndelag Health Study. (26th August 2022) - Smedbråten, Kaja; Grotle, Margreth; Jahre, Henriette; Richardsen, Kåre Rønn; Småstuen, Milada Cvancarova; Skillgate, Eva; Øiestad, Britt Elin
Abstract: Background: There is limited knowledge on the association between lifestyle behaviour in adolescence and musculoskeletal pain in young adulthood. This study aimed to investigate whether an accumulation of adverse lifestyle behaviours in adolescents with and without musculoskeletal pain at baseline, was associated with persistent musculoskeletal pain (pain duration ≥3 consecutive months the last year) 11 years later. Methods: Longitudinal data from the Trøndelag Health Study in Norway including 1824 adolescents (13–19 years old) was analysed. The outcome was persistent musculoskeletal pain (≥3 months). The number of adverse lifestyle behaviours (low physical activity level, sleep problems, insufficient fruit/vegetables consumption, smoking, frequent alcohol intoxication [drunkenness] and/or illicit drug use) were summed up to comprise an ordinal variable and analysed with 0 or 1 adverse behaviours as the reference. Multiple logistic regression analyses, stratified by individuals with and without baseline musculoskeletal pain, were conducted. The results were expressed as odds ratios (ORs) with 95% confidence intervals (CIs). Results: In adolescents with musculoskeletal pain at baseline, reporting ≥ four adverse lifestyle behaviours increased the odds of persistent musculoskeletal pain (OR 2.23, 95% CI 1.36, 3.66) 11 years later. Two and three adverse behaviours were not associated with future persistent musculoskeletal pain. In adolescents without musculoskeletal pain at baseline, an accumulation of adverse lifestyle behaviours was not associated with future persistent musculoskeletal pain. Conclusion: An accumulation of adverse lifestyle behaviours in adolescents with musculoskeletal pain at baseline was associated with persistent musculoskeletal pain 11 years later, but not in adolescents without musculoskeletal pain at baseline. Significance: An accumulation of four or more adverse lifestyle behaviours in adolescents with musculoskeletal pain was associated with persistent musculoskeletal pain in young adulthood. In future health care of adolescents with musculoskeletal pain, lifestyle behaviours should be assessed, with emphasis on accumulation of multiple adverse lifestyle behaviours. Focusing on an accumulation of multiple adverse lifestyle behaviours, rather than each individual behaviour, might provide a potential area for future research and interventions targeting musculoskeletal pain in youth.